Participación de las Tiorredoxinas en la digestión de proteínas vegetales : relación Soja (Glycine max) - Anticarsia gemmatalis - Tejedor, María Daniela (2017)
Soybean increases the expression of GmIP as defense against A. gemmatalis attack.\nHowever, A. gemmatalis tolerates GmIP and feeds on soybean. In vitro experiments\nshown that human Trx reduces disulfide bonds present in soybean IP, BBI and KTI inactivating them. These results led to the hypothesis "thioredoxins in the guts of A.\ngemmatalis larvae inactivate soybean IP by reducing them, which allows them to feed\non soybean without affect their growth and development". A. gemmatalis larvae from\nneonate to 5th stage were fed on either artificial diets or soybean plants with different\nconcentrations of GmIP, and showed different parameters of growth and development.\nCaterpillar survival and weight were decreased, but larvae were able to adapt to the\npresence of GmIP in diet, maintaining gut enzymatic activity by overexpressing\ndigestive trypsin genes, which were sequenced and cloned. In addition, A. gemmatalis\nTrx was sequenced and, it was found that Trx was overexpressed in the gut of larvae in\nresponse to GmIP. AgTrx was capable to deactivate the GmIP in in vitro experiments,\nsuggesting a new mechanism of defense against GmIP.